2022
DOI: 10.1002/jso.27135
|View full text |Cite
|
Sign up to set email alerts
|

Extended postoperative thromboprophylaxis after pancreatic resection for pancreatic cancer is associated with decreased risk of venous thromboembolism in the minimally invasive approach

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is associated with increased venous thromboembolism (VTE). We sought to compare rates of bleeding complications and VTE in patients receiving extended postoperative thromboprophylaxis (EPT) to those who did not, and identify risk factors for VTE after pancreatectomy for PDAC.Methods: This is a retrospective review of pancreatectomies for PDAC. EPT was defined as 28 days of low molecular weight heparin. Multivariable analysis (MVA) was performed to identify in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…A few studies investigated thromboprophylaxis following pancreatic surgery for PDAC, and confirmed the efficacy of the general guidelines, which is that extended thromboprophylaxis was safe and did not increase the risk of PPH [83,116,117]. However, most studies were retrospective and varied in the VTE outcomes analyzed.…”
Section: Postoperative Thromboprophylaxis In Patients With Resectable...mentioning
confidence: 92%
“…A few studies investigated thromboprophylaxis following pancreatic surgery for PDAC, and confirmed the efficacy of the general guidelines, which is that extended thromboprophylaxis was safe and did not increase the risk of PPH [83,116,117]. However, most studies were retrospective and varied in the VTE outcomes analyzed.…”
Section: Postoperative Thromboprophylaxis In Patients With Resectable...mentioning
confidence: 92%